132k views
1 vote
What is the solution to the equations 3(x + 2) = 2(x + 5)

User MCB
by
5.6k points

1 Answer

1 vote

First, we apply the distributive property of multiplication:


\begin{gathered} 3x+3\cdot2=2x+2\cdot5, \\ 3x+6=2x+10. \end{gathered}

Now, subtracting 2x from the above equation we get:


\begin{gathered} 3x+6-2x=2x+10-2x, \\ x+6=10. \end{gathered}

Finally, subtracting 6 from the above equation we get:


\begin{gathered} x+6-6=10-6, \\ x=4 \end{gathered}

Answer:


x=4.

User Anup
by
5.3k points